PRELIMINARY REVISIONS OF SOME GENERA OF MALAYSIAN PAPILIONACEAE II - MS van Meeuwen; CGGJ van Steenis; J Stemmerik (Research Center for Biology, 1961)
The revisions or notes have been prepared by Miss M. S. van Meeuwen, except for those of Pseudarthria and Sophora by C. G. G. J.van Steenis, and Tephrosia by J. Stemmerik. In Alysicarpus 4 species are distinguished in Malaysia; a key, synonymy, and discussion are given.Lourea Desv., being a homonym, has, according to Dr. Bakhuizen van den Brink, to be replaced by Christia; a key and discussion is given of 4 Malaysian species; 5 new combinations are proposed. Under Desmodium the variability of D. heterocarpon (L.) DC. and its full synonymy are discussed; one new variety is proposed; an enumeration of specimens of both varieties is given. D. ormooarpoides DC. and D. zonatum Miq. are two sharply distinct species which have been confused in the past; a key, synonyms, discussion, and enumeration of specimens are provided. The discrimination of D. sequax Wall, and D. viegaphyllum Zoll. is discussed and their synonymy given; specimens have been enumerated. Distribution is given of D. scorpiurus (Sw.) Desv. and D. tor-tuosum (Sw.)DC. Psoraleai is revised for Malaysia where 4 species are recorded and keyed out; a fifth species must remain dubious, as the type could not be traced in the Paris Herbarium. Of Pseudarthria only one species occurs in Malaysia; its synonymy and distribution is given.Sophora longipes Merr.; an endemic species from the Philippines, is recorded for Timor. Of Tephro&ia maculata M. & P., from Papua, the synonymy is given and specimens enumerated; T. brachystachys Laut. & K. Seh. is reduced. Notes and distribution are given of T. zollingeri Backer. For T. mollie . Val., a later homonym, the new name T. papuana is proposed.